Estimated GFR With Cystatin C and Creatinine in Clinical Practice: A Retrospective Cohort StudyPlain-Language Summary - Eric Raphael Gottlieb; Christopher Estiverne; Nicole V. Tolan; Stacy E.F. Melanson; Mallika L. Mendu (Kidney Medicine, 2023)
Rationale & Objective: Estimation of glomerular filtration rate (eGFR) and staging of chronic kidney disease (CKD) are essential to guide management. Although creatinine is routinely used, a recent national task force recommended the use of cystatin C for confirmation. The objective of this study was to examine the following parameters: (1) how cystatin C correlates with creatinine eGFR; (2) how it indicates differences in CKD staging; and (3) how it may affect kidney care delivery. Study Design: Retrospective observational cohort study. Setting & Participants: 1,783 inpatients and outpatients who had cystatin C and creatinine levels drawn within 24 hours at Brigham Health-affiliated clinical laboratories. Predictors: Serum creatinine levels, basic clinical/sociodemographic variables, and reasons for ordering cystatin C from a structured partial chart review. Analytical Approach: Univariate and multivariable linear and logistic regression. Results: Cystatin C-based eGFR was very strongly correlated with creatinine-based eGFR (Spearman correlation ρ = 0.83). Cystatin C eGFR resulted in a change to a later CKD stage in 27%, an earlier stage in 7%, and no change in 66% of patients. Black race was associated with a lower likelihood of change to a later stage (OR, 0.53; 95% CI [0.36, 0.75]; P < 0.001), whereas age (OR per year OR, 1.03; 95% CI [1.02, 1.04]; P < 0.001) and Elixhauser score (OR per point OR, 1.22; 95% CI [1.10, 1.36]; P < 0.001) were associated with a higher likelihood of change to a later stage. Limitations: Single center, no direct measurement of clearance for comparison, and inconsistent self-identification of race/ethnicity. Conclusions: Cystatin C eGFR correlates strongly with creatinine eGFR but can have a substantial effect on CKD staging. As cystatin C is adopted, clinicians must be informed on this impact.